Detection of collagens by multispectral optoacoustic tomography as an imaging biomarker for Duchenne muscular dystrophy - Regensburger, Adrian; Fonteyne, Lina M.; Jüngert, Jörg; Wagner, Anna; Gerhalter, Teresa; Nagel, Armin Michael; Heiß, Rafael; Flenkenthaler, Florian; Qurashi, Matthias; Neurath, Markus; Klymiuk, Nikolai; Kemter, Elisabeth; et al. (Nature Medicine, 2019)
Biomarkers for monitoring of disease progression and response to therapy are lacking for muscle diseases such as Duchenne muscular dystrophy. Noninvasive in vivo molecular imaging with multispectral optoacoustic tomography (MSOT) uses pulsed laser light to induce acoustic pressure waves, enabling the visualization of endogenous chromophores. Here we describe an application of MSOT, in which illumination in the near- and extended near-infrared ranges from 680–1,100 nm enables the visualization and quantification of collagen content. We first demonstrated the feasibility of this approach to noninvasive quantification of tissue fibrosis in longitudinal studies in a large-animal Duchenne muscular dystrophy model in pigs, and then applied this approach to pediatric patients. MSOT-derived collagen content measurements in skeletal muscle were highly correlated to the functional status of the patients and provided additional information on molecular features as compared to magnetic resonance imaging. This study highlights the potential of MSOT imaging as a noninvasive, age-independent biomarker for the implementation and monitoring of newly developed therapies in muscular diseases.
CRIS-Team Scopus Importer:2019-12-17